Al/p-Si/CuPc/Al FOTODIYOTLARIN FOTOVOLTAIK İNCELENMESI - Güngör, Zöhre Görünmez; Coşkun, Burhan; İlhan, Mustafa; Koç, Mümin Mehmet (Kirklareli University, 2023)
Ftalosiyanin, nonlineer optik cihazlar, elektrofotografik uygulamalar, fotodinamik terapi uygulamaları, infrared uygulamaları, sensör uygulamaları ve katalizör uygulamaları gibi birçok bilimsel ve endüstriyel alanlarda kullanılmaktadır. Ftalosiyanin molekülünün heterobileşimli yapılarda uygulamaları daha önceden çalışılmış bulunmaktadır. Elde edilen sonuçlar, ftalosiyanin fotodedektör ve fotodiyot uygulamalarında kullanılabileceğini ortaya çıkarmıştır. Organik dedektörler esnek yüzeylere uygulanabilirler ve üretim maliyetleri metal esaslı fotodedektörlere göre daha düşüktür. Organik dedektörlerin bu özellikleri göz önüne alınarak projemizde bakır-ftalosiyanin tuzları kullanılarak ftalosiyanin temelli organik fotodiyotlar üretilmiştir. Üretilen Al/p-Si/CuPc/Al fotodiyotların optoelektronik özellikleri araştırılmış, I – V, I – t ve fototepki davranışları değerlendirilmiştir.

Phthalocyanine is used in many scientific and industrial fields such as nonlinear optical devices, electrophotographic applications, photodynamic therapy applications, infrared applications, sensor applications and catalyst applications. The applications of the phthalocyanine molecule in hetero-compound structures have been studied before. The obtained results revealed that phthalocyanine can be used in photodetector and photodiode applications. Organic detectors can be applied to flexible surfaces and their production costs are lower than metal-based photodetectors. Considering these features of organic detectors, phthalocyanine-based organic photodiodes were produced by using copper-phthalocyanine salts in our project. The optoelectronic properties of the produced Al/p-Si/CuPc/Al photodiodes were investigated, and their I – V, I – t, and photoresponsivity behaviours were evaluated. Since I-V measurements show that the current changes with the increase of illumination intensities, our study shows that Al/p-Si/CuPc/Al structures have photodiode properties.
PHOTOVOLTAIC INVESTIGATION OF Al/p-Si/CuPc/Al PHOTODIODES
Keywords: Engineering; Mühendislik